Adaptive Protection Coordination Scheme Using Numerical Directional Overcurrent Relays - Alam, Mahamad Nabab (IEEE transactions on industrial informatics, 2019)
Dynamically changing distribution system operating conditions compromises the coordination of the existing protection schemes. This paper proposes an online adaptive protection coordination scheme by utilizing numerical directional overcurrent relays (DOCRs) and commercial A Mathematical Programming Language (AMPL) based Interior Point OPTimization (IPOPT) solver. The proposed scheme also utilizes intelligent electronic devices and a communication channel to obtain real-time system information and to update relays settings. The presented approach is able to handle different operating conditions of the system, including loss of loads, generations, and lines. Further, the miscoordination arising due to injections of distributed generations (DGs) is also handled. The proposed approach has been tested on the IEEE 14-bus system (with and without DG), under various operating conditions. Overall system reliability enhancement using the proposed approach has been analyzed in terms of the amount of energy not supplied. Further, the optimum settings of DOCRs obtained using AMPL based IPOPT solver has been compared with those obtained by General Algebraic Modeling System based Sparse Nonlinear OPTimizer solver, OPTI Toolbox based IPOPT solver, MATLAB based interior point method, and metaheuristic genetic algorithm and differential evolution. It has been found that the proposed coordination approach gives good results in reasonably small time and thus, is suitable for the adaptive protection scheme.